Psychometric properties of a romantic jealousy scale in university students - Arias Gallegos, Walter L. (2021)
In the following research it has been analyzed the psychometrical properties of the Jealousy Intensity Measure Scale in Arequipa city, so there were assessed 212 university students from a private university located in Arequipa. The data was processed through SPSS and Factor programs. The results indicate that the test presents a bifactorial structure which is related with external and internal factors about jealousy, with adequate reliability indexes (α= 0.880 and α= 0.925, respectively). Both factors explain the 44.1% of the total variance of the test and present satisfactory goodness of fit indexes in the major cases.